2024
DOI: 10.1021/acs.jpcb.3c05531
|View full text |Cite
|
Sign up to set email alerts
|

Disruption Mechanisms of Enveloped Viruses by Ionic and Nonionic Surfactants

Geetanjali Negi,
Anurag Sharma,
Monika Chaudhary
et al.

Abstract: The world has witnessed multiple pandemics and endemics caused by enveloped viruses in the past century. To name a few, the ongoing COVID-19 pandemic and other pandemics/endemics caused by coronaviruses, influenza viruses, HIV-1, etc. The external and topical applications of surfactants have been effective in limiting the spread of viruses. While it is well-known that surfactants inactivate virus particles (virions), the mechanism of action of surfactants against enveloped virions has not yet been established.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 60 publications
(107 reference statements)
0
0
0
Order By: Relevance
“…The premature Env activation ultimately leads to irreversible deactivation of viral entry machinery. , Recently, Pu et al constructed a novel small-molecule HIV-1 inactivator named FD028 through conjugating a small CD4 mimetic to a gp41-targeting fusion inhibitor . In addition to these CD4-mimetic molecules, the virucidal effect of several surfactants has been confirmed. , Although strategies mentioned above are promising, the safety of small-molecule drugs requires extensive evaluation. For instance, it has been revealed that some CD4 mimetic small molecules can enhance HIV-1 infection of CD4 – /CCR5 + cells, thus having adverse effects on the otherwise normally functioning immune system .…”
Section: Introductionmentioning
confidence: 99%
“…The premature Env activation ultimately leads to irreversible deactivation of viral entry machinery. , Recently, Pu et al constructed a novel small-molecule HIV-1 inactivator named FD028 through conjugating a small CD4 mimetic to a gp41-targeting fusion inhibitor . In addition to these CD4-mimetic molecules, the virucidal effect of several surfactants has been confirmed. , Although strategies mentioned above are promising, the safety of small-molecule drugs requires extensive evaluation. For instance, it has been revealed that some CD4 mimetic small molecules can enhance HIV-1 infection of CD4 – /CCR5 + cells, thus having adverse effects on the otherwise normally functioning immune system .…”
Section: Introductionmentioning
confidence: 99%